Permanenter Notstand und der Kampf um gute Sorge(arbeit) - Polanyi'sche Doppelbewegungen in der Marktgesellschaft; Constant state of emergency and the struggle for good care (work) - Polanyian double movements in neoliberalism - Fabienne Dećieux; Karina Becker; Yalcin Kutlu (Industrielle Beziehungen, 2019)
Der Artikel untersucht kollektives Interessenhandeln in der (Klein-)Kinderbetreuung in Deutschland und Os̈terreich. Mit der Polanyi'schen Figur der Doppelbewegung werden die Dynamiken der aktuellen Aushandlungen im Feld der Sorge und Sorgearbeit aufeinander bezogen und analytisch gefasst. Die Bewegung in Form einer (Quasi-)Vermarktlichung steht im Spannungsverhal̈tnis zum ausgeprag̈ten Berufsethos der ErzieherInnen, um das sie durch Proteste (Os̈terreich) und Streiks (Deutschland) kam̈pfen. – – The article examines collective interests and collective action in (early) childcare in Germany and Austria. With the Polanyian concept of the double movement, the dynamics of the current negotiations in the field of care work are related to each other and summarized analytically. The movement in the form of (quasi) marketization is conflicting with the strong professional ethos of the care workers in the field of (early) child care. Protests (Austria) and strikes (Germany) for decent care and working conditions are evolving around this tension.
Keywords: B54; D63; J81; 330; (Klein-)Kinderbetreuung; Sorgearbeit; Polanyi; (Quasi-)Vermarktlichung; Industrielle Beziehungen; (Early) Child care; care work; Polanyi; (quasi) marketization; Industrial Relations